2021
DOI: 10.1111/bjop.12505
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive adolescents: The relationship between weekly life events and weekly socioemotional well‐being

Abstract: Recent research into Person x Environment interaction has supported the view that sensitivity to environmental influences is a susceptibility factor rather than a vulnerability factor. Given this perspective, this study examined the role of the adolescent's sensory-processing sensitivity in the context of weekly life events and weekly socioemotional well-being. In the study, 114 adolescents repeatedly self-reported their sensitivity, recent life events, and recent socioemotional well-being in four surveys at o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…Overall, previous recent studies stated the need for the assessment of the level of SPS traits [ 7 ], due to the high prevalence rates of high sensitivity in the general population [ 11 , 54 ]. In fact, researchers pointed out the impact of different levels in SPS on school performance, health and quality of life in children [ 7 , 55 , 56 , 57 ]. Therefore, assessment instruments have a great variety of advantages because they can be administered quickly and easily, reducing time and human costs [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, previous recent studies stated the need for the assessment of the level of SPS traits [ 7 ], due to the high prevalence rates of high sensitivity in the general population [ 11 , 54 ]. In fact, researchers pointed out the impact of different levels in SPS on school performance, health and quality of life in children [ 7 , 55 , 56 , 57 ]. Therefore, assessment instruments have a great variety of advantages because they can be administered quickly and easily, reducing time and human costs [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to their traits, highly sensitive young people are more likely to experience poor mental health in negative environments. For example, recent evidence has shown that compared to less sensitive adolescents, highly sensitive adolescents experience lower socio-emotional wellbeing when the impact of negative life events experienced in the preceding week was significant (Iimura, 2021). Moreover, several cross-sectional studies have reported that high sensoryprocessing sensitivity in adolescents is positively correlated with depressive symptoms and anxiety (Liss et al, 2005;2008).…”
Section: Individual Differences In Environmental Sensitivitymentioning
confidence: 99%
“…For example, Pluess et al (2010) reported that individuals with the 5-HTTLPR s-allele, a genetic marker of environmental sensitivity, have a higher tendency toward developing the Big Five of neuroticism when they experience negative life events. In addition, Iimura (2021) indicated that when highly sensitive youths have recently experienced positive life events, there is no observable decline in their socio-emotional well-being. The key implication of these findings or theories regarding environmental sensitivity is that highly sensitive youths are not necessarily vulnerable individuals.…”
Section: Is Sensitivity a Vulnerability Amidst The Covid-19 Pandemic?mentioning
confidence: 99%
“…Second, highly sensitive individuals are more likely to be adversely affected by daily hassles and recent negative life events (e.g., Iimura, 2021). They may also be more prone to develop gastrointestinal disease symptoms due to stressful environmental factors.…”
Section: Why Did Highly Sensitive Persons Report Gastrointestinal Disease Symptoms?mentioning
confidence: 99%